Travels with George [large type] : in search of Washington and his legacy - Philbrick, Nathaniel (Random House Large Print, 2021)
Written at a moment when America's founding figures are under increasing scrutiny, the author, retracing George Washington's journey as a new president through all thirteen former colonies, paints a picture of eighteenth-century America as divided and fraught as it is today.